2005
DOI: 10.1021/es051270q
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Loading into Surface Water along a Hydrological, Biogeochemical, and Land Use Gradient:  A Holistic Watershed Approach

Abstract: Identifying the sources and impacts of organic and inorganic contaminants at the watershed scale is a complex challenge because of the multitude of processes occurring in time and space. Investigation of geochemical transformations requires a systematic evaluation of hydrologic, landscape, and anthropogenic factors. The 1160 km2 Boulder Creek Watershed in the Colorado Front Range encompasses a gradient of geology, ecotypes, climate, and urbanization. Streamflow originates primarily as snowmelt and shows substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
99
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 66 publications
14
99
0
Order By: Relevance
“…Barber et al (2006) found lithium to be a good indicator of anthropogenic waste inputs into streams, consistent with this study. Lithium is a drug used for the treatment of mood disorders (Price and Heninger 1994).…”
Section: Discussionsupporting
confidence: 90%
“…Barber et al (2006) found lithium to be a good indicator of anthropogenic waste inputs into streams, consistent with this study. Lithium is a drug used for the treatment of mood disorders (Price and Heninger 1994).…”
Section: Discussionsupporting
confidence: 90%
“…Urbanization in arid and semi-arid regions can negatively impact stream and drinking water quality by increasing loads of nutrients, metals and organic pollutants to surface and ground water (Asaf et al, 2004;Barber et al, 2006;Carlson, 2004;Gallo et al, 2012;e.g. Hamilton et al, 2004;Lewis and Grimm, 2007), yet little is known regarding how the characteristics of the stormwater drainage system, and specifically the characteristics of the stream channel substrate, alter urban runoff hydrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The boron concentrations of surrounding irrigated soils before the waste water discharges began were 0.15 ppm (0-20 cm depth) and 0.19 ppm (80-100 cm depth), while after the discharges, the boron concentrations were 13.90 ppm (0-20 cm depth) and 3.66 ppm (80-100 cm depth) (Akar 2007). Barber et al (2006) reported that daily loads of boron in the Boulder Creek, Colorado of 0-55 kg/day are mostly due to the effluent of the Boulder waste water treatment plant. Mumma et al (1984) reported that the boron concentration in sewage sludges from 23 U.S. cities ranged from 7.1 to 53.3 mg/kg.…”
Section: Soilmentioning
confidence: 98%